Spline wear life prediction considering multiple errors. (January 2022) - Zhao, Qingyan; Yu, Tianxiang; Pang, Tianyang; Song, Bifeng
Highlights: A spline clearance calculation method considering multiple errors is proposed. The relative sliding speed between spline contact surfaces is deduced. The contact area of the spline is derived from the equivalent model. A numerical model of spline wear with multiple errors is established. Abstract: Splines in aero-engine are often excessively worn, seriously affecting flight safety. Manufacturing errors and parallel offset lead to unequal tooth loads, which is one of the main reasons to reduce the spline wear life. However, spline wear life with multiple errors is sometimes hard to predict due to technical or cost reasons. To obtain a more realistic spline wear life, a spline clearance calculation method considering manufacturing errors and parallel offset is proposed. The tooth contact pressure is developed based on the equivalent model of force carried by each tooth. Then, the relative sliding speed between the tooth and the tooth space is deduced by equating the two contact points on the spline as a crank-slider mechanism. Finally, a numerical model of spline wear is established by using the improved Archard's wear model. The case results show that the maximum wear depth at torque of 240 N·m is 1.7 times the wear depth at torque of 80 N·m for the spline with a total of 2x10 5 motion cycles. For a spline with a parallel offset of 30 μm, the maximum wear depth is 66.8 μm, which is 3 times the offset of 5 μm. The wear life results show that the average life of the spline is 0.7 times that of parallel offset when considering multiple errors.